Developing A Natural Method To Practice The Pronunciation Of Arabic Sounds For The Speakers Of Malay Dialects In Southeast Asia/ تطوير طريقة طبيعية للتدرب على نطق الأصوات العربية لمتحدثي اللهجات الماليزية في جنوب شرق آسيا - Darmawaty, Ridha; Al-Ma'youf, Ali Mayouf; Nasaruddin, Nasaruddin; Lamri Banjar, Maimunah Dairani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Previous researchers, such as (Ahmad, 2017) (Maasiri, 2012), (Yusuf K. , 2019) and (Thayyib, 2017) have found consistent evidence that Malay learners often pronounce certain Arabic words not as native speakers do but in a way they get used to hearing those since their childhood. We offer a method for training the pronunciation of Arabic words using natural sounds. It employs the sounds from oneself and the natural or automatic sounds closest to the sounds to be instructed. This is a new model in Arabic pronunciation training for Malay communities in Southeast Asia through error analysis, contrastive studies, and observations. We argue that it is essential for those teaching or learning Arabic to develop linguistic proficiency and skills in correct pronunciation. It is also helpful for training in Qur'an recitation. We create this method using the literacy development, reflection, design, and development (R2D2) model. Three points are highlighted: (1) common errors in the pronunciation of Arabic sounds among the Malay communities in Southeast Asia concern the following sounds: tha, ha, kha, dha, shen, sad, dhaad, ain, ghain, fa, dan qaf., Ta, dan Dha; (2) the training includes three techniques: al-Muhaakat Aliyah (imitation of human-made sounds), al-Muhaakat Thabiiyyah (imitation of nature sounds), and al-Muhaakat bi an-Naathiq al-Ashly (imitation of Arabic native speakers); (3) video recordings are used to demonstrate the techniques for non-attending trainees.